Housing quality and risk of acute respiratory infections among hospitalized children under five in Ibadan, Nigeria. Issue 8 (December 2016) - Fakunle, Adekunle G; Ana, Godson R; Olaiya, Muideen T
Acute respiratory infection is the fourth major cause of morbidity and mortality among children under five globally. However, information on housing characteristics that could predispose children under five to these infections is scanty in Nigeria. Therefore, this study assessed the quality of housing and its contribution to the acquisition of acute respiratory infections among children under five in Ibadan. A prospective case–control design was employed for this study. Two hundred and twenty children under five each with acute respiratory infection (cases) and without acute respiratory infection (controls) were selected from children visiting Oni-memorial Children Hospital and University College Hospital, Ibadan. A survey of 66 consented cases and controls each was carried out using a checklist to assess indoor housing indicators. Data were analysed using descriptive statistics, Chi-square and logistic regression at p  < 0.05. More cases (43, 65.2%) than controls (28, 42.4%) reside in houses with poor housing quality (OR 2.5; 95% CI = 1.3–5.1). Presence of damp roof (OR 2.9; 95% CI = 1.1–8.1), mould growth on walls (OR 6.3; 95% CI = 2.0–19.6) and high indoor air relative humidity (OR 10.2; 95% CI = 3.0–35.2) were significant risk factors for acute respiratory infections in children under five. Inadequate housing conditions play an important role in the acquisition of acute respiratory infections. Therefore, considerable effort should be made to educate mothers of children under five on improved housing and hygiene conditions in order to reduce childhood morbidity and mortality risks associated with acute respiratory infections.